Pendampingan Hafalan Al-Qur’an dengan Metode Talaqqi bagi Siswa yang Belum Bisa Membaca Al-Qur’an - Mela Meliana; Rinesti Witasari (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This community service program aimed to assist students of SDN 4 Wagirlor in memorizing the Qur’an using the Talaqqi method. The background of this activity lies in the limited reading ability of some students who, despite not being fluent in reading the Qur’an, showed strong motivation to memorize it. The program applied the Asset-Based Community Development (ABCD) approach, emphasizing local assets such as Qur’an teachers, students’ enthusiasm, a supportive school environment, and the talaqqi method itself. The mentoring process was conducted through the stages of Discover, Dream, Design, Deliver, and Destiny, using talaqqi strategies based on direct interaction, verse repetition, and teacher correction. The results revealed that students found it easier to memorize by listening directly, felt more motivated when learning together, and were encouraged to complete the memorization of Juz 30. Furthermore, program sustainability was supported by the involvement of teachers, students, parents, and the school community. Thus, the Talaqqi method proved to be effective as a tahfidz learning model, enhancing students’ motivation, ability, and love for the Qur’an from an early age